2020
DOI: 10.3389/fmicb.2020.01191
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Protein Glycosylation on Campylobacter fetus Physiology

Abstract: Campylobacter fetus is commonly associated with venereal disease and abortions in cattle and sheep, and can also cause intestinal or systemic infections in humans that are immunocompromised, elderly, or exposed to infected livestock. It is also believed that C. fetus infection can result from the consumption or handling of contaminated food products, but C. fetus is rarely detected in food since isolation methods are not suited for its detection and the physiology of the organism makes culturing difficult. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 74 publications
0
8
1
Order By: Relevance
“…Functional analysis of the PglI proteins was carried out by reconstituting the C. jejuni N-glycosylation system in the E. coli three-plasmid system by complementing the pglI gene mutation on plasmid pACYC184 pgl /Δ pglI (as described in ref ). Plasmid pACYC184 pgl (expressing all components of the N-glycosylation pathway for biosynthesis of the full-length Cj -N-glycan/heptasaccharide) and pACYC184 pgl /Δ pglI complemented with pglI from Cj- 81116 were used as positive controls.…”
Section: Resultscontrasting
confidence: 72%
See 2 more Smart Citations
“…Functional analysis of the PglI proteins was carried out by reconstituting the C. jejuni N-glycosylation system in the E. coli three-plasmid system by complementing the pglI gene mutation on plasmid pACYC184 pgl /Δ pglI (as described in ref ). Plasmid pACYC184 pgl (expressing all components of the N-glycosylation pathway for biosynthesis of the full-length Cj -N-glycan/heptasaccharide) and pACYC184 pgl /Δ pglI complemented with pglI from Cj- 81116 were used as positive controls.…”
Section: Resultscontrasting
confidence: 72%
“…The pglI expression plasmid from Cj strain 81116 has been described previously . GEMS strain pglIs were PCR amplified (in triplicate) from chromosomal DNA (cDNA) from strains 1J2, 1J5, 1H2, and 1D7 with oligonucleotides (pglI-81116- Bam HI-F) and (81116-pglI-XhoI-R_short).…”
Section: Experimental Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Within the highly conserved N -linked general protein glycosylation pathway (Pgl), more than 80 proteins have been identified so far in C. jejuni which are characterized by a typical heptasaccharide motif (GalNAc-α1,4-GalNAc-α1,4-(Glc-β1,3-)GalNAc-α1,4-GalNAc-α1,4-GalNAc-α1,3-diNAcBac-β1; with diNAcBac as 2,4-diacetamido-2,4,6-trideoxyglucopyranose, Gal as galactose, NAc as N-acetylated carbohydrate, Glc as glucose) attached to asparagine residues (Cain et al 2019 ; Duma et al 2020 ). The consensus sequence of the glycosylation sites for efficient modifications by bacterial oligosaccharyltransferases is D/E—Y—N—X—S/T, with Y and X being variable amino acids except proline (Kowarik et al 2006 ).…”
Section: Adhesion: the First Step For Attacking Host Cellsmentioning
confidence: 99%
“…The discovery of a general protein glycosylation (Pgl) system in C. jejuni , and related organisms also confirmed that bacteria are capable of modifying a diverse array of proteins with N -glycans. The biochemistry of N -glycosylation in C.…”
Section: Introductionmentioning
confidence: 99%